2018
DOI: 10.1080/07853890.2018.1489142
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress in ischemic and nephrotoxic acute kidney injury

Abstract: Acute kidney injury (AKI) is a medical condition characterized by kidney damage with a rapid decline of renal function, which is associated with high mortality and morbidity. Recent research has further established an intimate relationship between AKI and chronic kidney disease. Perturbations of kidney cells in AKI result in the accumulation of unfolded and misfolded proteins in the endoplasmic reticulum (ER), leading to unfolded protein response (UPR) or ER stress. In this review, we analyze the role and regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
106
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 97 publications
4
106
0
Order By: Relevance
“…The er is an intracellular organelle that serves an important role in protein homeostasis (14). The er can restore homeostasis via the uPr.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The er is an intracellular organelle that serves an important role in protein homeostasis (14). The er can restore homeostasis via the uPr.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the development of anti-inflammatory and anti-apoptotic drugs to manage cP-induced renal injury (8,13). The endoplasmic reticulum (er) can serve a critical role in cP cellular toxicity (13,14). The er is the organelle responsible for synthesis and maturation of proteins, calcium storage and maintenance of cell homeostasis (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we demonstrated that FGF2 could protect against renal I/R injury via attenuation of mitochondrial damage and HMGB1/TLR2-mediated inflammatory response (Tan et al, 2017). In addition, other findings revealed that ER stress is involved in AKI triggered by renal I/R injury and nephrotoxic drugs (Gallazzini and Pallet, 2018;Yan et al, 2018). Many studies have reported that ER stress could trigger inflammatory responses and regulate mitochondrial metabolic status through the UPR signaling pathway (Bronner et al, 2015;So, 2018;Gallazzini and Pallet, 2018;Inoue et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…ER stress has been implicated in causing ischemic and nephrotoxic acute kidney injury (AKI) 20 . The CORE is an attractive target for gentamicin-induced proteotoxicity because ER-mitochondrial collaboration prevents the toxic protein misfolding that accompanies normal protein synthesis 19 .…”
Section: Introductionmentioning
confidence: 99%